Optimasi Pertumbuhan dan Hasil Jagung (Zea mays L.) dengan Pupuk Ammonium Klorida pada Dataran Rendah - Fidiyawati, Eni; Cahyono, Tri; Setyorini, Dwi (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2024)
The high yield gap between the potential of varieties and the real production of corn in the field is one of the problems in meeting the national corn needs, so various efforts to increase productivity are continuously carried out, one of which is the application of inorganic fertilizers that are suitable for plant needs and specific. The study was conducted at KP Mojosari AIAT East Java from November 2020 to February 2021. The experiment used a randomized block design (RAK) with 5 replications and 6 treatments including control (without fertilizer) and 5 other treatments which were a combination of the dose of ammonium chloride fertilizer and the dose of urea fertilizer. The results showed that treatment F showed the highest yields on plant height and canopy width, treatment E showed best results on leaf width variables, and treatment C showed the highest results on stem diameter variables. Meanwhile, result parameter shows that all treatment combinations obtained higher results than the control. The conclusion is that this ammonium chloride fertilizer can be used for corn because it has an additional Cl element which is useful for the efficient use of nitrogen in plants, but the application of Cl must be limited